KEANEKARAGAMAN DAN DOMINANSI RUMPUT LAUT HIDROKOLOID PADA SUBSTRAT YANG BERBEDA DI PERAIRAN PANTAI KARANGTENGAHNUSAKAMBANGAN CILACAP - Bayu Ardiyanto; Achmad Ilalqisny Insan; Dwi Sunu Widyartini (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
The waters of Karangtengah Nusakambangan Cilacap have various types of substrates, namely sand, coral and mixture. Beach conditions with many types of substrates allow various species of seaweed to grow. Information regarding the diversity and dominance of seaweed producing hydrocolloid species has not been much studied in the waters of Karangtengah Beach. This study aims to determine the diversity and dominance of seaweed producing hydrocolloids on different substrates in the waters of Karangtengah Nusakambangan Cilacap. This study uses a survey method with a sampling technique that is the selected random transect method. Six transect lines were made perpendicular to the coastline and the distance between transects was 25 m. Each transect was made three plots, each plot measuring 1x1 m based on the substrate (coral, sand, and mixture). The main parameters observed were the amount of biomass and the number of species. Supporting parameters observed were environmental factors namely temperature, salinity, pH, current speed and depth. The number of hydrocolloid seaweed species found was 10 species of seaweed with details of 5 alginate-producing species, 3 agar-producing species, and 2 carrageenan-producing species. The diversity index value in the coastal waters of Karangtengah between 0,6-2,0 was classified as moderate diversity. The dominance index value in the coastal waters of Karangtengah between 0,2-0,6 was classified as low dominance.